Variational FEM Approach to the Study of Drug Distribution in Dermal Layers in Transdermal Drug Delivery System - Pradhananga, S. P. (SCITECH Nepal, 2020)
Today about 75% of drugs are taken orally and are found not to be as effective as desired. To improve this, transdermal drug delivery system was emerged. Transdermal drug delivery is self-contained continuous dosage forms which, when applied to the intact skin, delivers the drug through the skin at controlled rate to the systemic circulation. The present model describes the diffusion of drugs in transdermal drug delivery system. The tissue absorption rate and drug intake rate by blood are taken in an account. The Finite Element Method (FEM) approach is used for the solution with four layers of skin which are taken as discretized elements. The numerical calculation and plotting graphs have been done by using MATLAB.